Protecting the regenerative environment: selecting the optimal delivery vehicle for cartilage repair—a narrative review - Campbell, T. Mark; Trudel, Guy (Frontiers in Bioengineering and Biotechnology, 2024)
Focal cartilage defects are common in youth and older adults, cause significant morbidity and constitute a major risk factor for developing osteoarthritis (OA). OA is the most common musculoskeletal (MSK) disease worldwide, resulting in pain, stiffness, loss of function, and is currently irreversible. Research into the optimal regenerative approach and methods in the setting of either focal cartilage defects and/or OA holds to the ideal of resolving both diseases. The two fundamentals required for cartilage regenerative treatment are 1) the biological element contributing to the regeneration (e.g., direct application of stem cells, or of an exogenous secretome), and 2) the vehicle by which the biological element is suspended and delivered. The vehicle provides support to the regenerative process by providing a protective environment, a structure that allows cell adherence and migration, and a source of growth and regenerative factors that can activate and sustain regeneration. Models of cartilage diseases include osteochondral defect (OCD) (which usually involve one focal lesion), or OA (which involves a more diffuse articular cartilage loss). Given the differing nature of these models, the optimal regenerative strategy to treat different cartilage diseases may not be universal. This could potentially impact the translatability of a successful approach in one condition to that of the other. An analogy would be the repair of a pothole (OCD) versus repaving the entire road (OA). In this narrative review, we explore the existing literature evaluating cartilage regeneration approaches for OCD and OA in animal then in human studies and the vehicles used for each of these two conditions. We then highlight strengths and challenges faced by the different approaches presented and discuss what might constitute the optimal cartilage regenerative delivery vehicle for clinical cartilage regeneration.